Analysis of the Implementation and Impact of Green Accounting on the Profitability of the Tofu Factory in Kuamang Ujung Gading Village, West Pasaman District - Tia Yosiska; Yenni Samri Juliati Nasution; Kusmilawaty Kusmilawaty (Pusat P2M Politeknik Negeri Batam, 2024)
This research aims to assess the implementation of Green Accounting in managing waste produced by tofu factories and to examine the impact of expenditure costs resulting from Green Accounting implementation on the profitability of the Tofu Factory in Kuamang Ujung Gading Village, West Pasaman District. Primary data serves as the source for this study. Data collection methods include observation, interviews, documentation, and surveys conducted at the research site using qualitative descriptive methodology. Findings indicate suboptimal implementation of Green Accounting at the Kuamang Ujung Gading Tofu Factory, focusing solely on solid waste such as tofu dregs, which are resold for animal feed, while liquid waste remains untreated, with only two wastewater storage ponds available. Insufficient capacity in treating tofu wastewater leads to overflow during rainfall, contaminating nearby water bodies and agricultural lands. Additionally, the factory lacks recording reports on expenses related to tank or holding pond construction, thus hindering an accurate assessment of their impact on business profitability.